Morphometric parameters of seeds as a practical method for identifying rare species of the genus Tulipa L. (Liliaceae) from East Kazakhstan region - Aidar A. Sumbembayev; Olga Lagus; Alevtina N. Danilova; Agnieszka Rewicz; Sławomir Nowak (PhytoKeys)
The genus Tulipa includes some of the most important ornamental plants. The aim of this work was to study the seed morphology of Tulipa species from East Kazakhstan, including seed coat structure. An analysis focused on five taxa from various natural environmental conditions. A total of 31 tulip populations were studied to establish morphological variability. Preliminary analyses of the importance of habitat-related ecological factors have been carried out. The results of this study provide new qualitative characteristics for distinguishing closely related species and are discussed in relation to their systematic relationships. The structure of the seed coat was studied by Scanning Electron Microscopy; however, the results did not show significant variability. An identification key to determine the species of tulips in East Kazakhstan is proposed.